Flow Cytometric Quantification of Granulocytic Alkaline Phosphatase Activity in Unlysed Whole Blood. Issue 1 (16th June 2020) - Bardina, Jorge; Rico, Laura G.; Ward, Michael D.; Bradford, Jolene A.; Juncà, Jordi; Petriz, Jordi
Abstract: Translational research has improved the diagnosis and follow‐up of hematological diseases and malignancies. However, some classical diagnostics used for research and clinical practice that have remain practically unchanged for decades may be better addressed through advances in flow cytometry technology, whereby more precise measurements may be implemented in a straightforward manner. The current method for semiquantitative analysis of granulocytic alkaline phosphatase (GAP) activity is still based on observer‐dependent color‐intensity classification. Here, we describe a novel strategy for flow cytometric quantification of GAP activity in which staining and analytical flow cytometry facilitate the detection and quantification of subpopulations of leukocytes with different GAP activities. Our experiments demonstrate the potential of flow cytometry as a simple and highly sensitive approach for measuring GAP activity in unlysed whole blood. Notably, a comparison of flow cytometry and enzyme cytochemistry techniques showed that enzyme activity scores were not similar, indicating that results needs to be interpreted with caution, given that the enzyme‐substrate binding affinities may differ, as well as the subjective evaluation of the intensity of the precipitated dye. © 2020 Wiley Periodicals LLC. Basic Protocol : Protocol preparation, sample acquisition, and gating strategy for flow cytometric identification of alkaline phosphatase activity in granulocytes from whole blood samples Support Protocol 1 : Sample preparation for granulocyte alkaline phosphatase determination by flow cytometry using no‐lyse no‐wash methods Support Protocol 2 : Data analysis and formula to calculate the GAP score